CONJUNCTIONS IN INDONESIAN UNDERGRADUATE THESIS ABSTRACTS - Ruri Fadhilah Kurniati (ETNOLINGUAL, 2019)
This study investigates how conjunctions are used for organizing ideas in abstracts of linguistics and literature theses written by undergraduate students of English Department in an Indonesian university. It also reveals the similarities in the ways conjunctions being used in the abstracts. It employs descriptive qualitative design to examine 82 abstracts which have been collected from 41 linguistics and 41 literature theses. The abstracts are analyzed by classifying and calculating the use of conjunctions using conjunctions taxonomy proposed by Halliday and Matthiessen (2014). The study finds that six abstracts do not apply conjunctions. While the rest use the three types of conjunctions: elaboration, extension, and enhancement. Elaborating conjunctions are used appropriately, whereas extending and enhancing conjunctions are partly inappropriately. Two kinds of inappropriate uses of conjunctions are misuse and overuse. The use of conjunctions in abstracts of linguistics and literature theses is quite similar in the ways they are used and total number of their uses. Certain conjunctions are present in the abstracts, while the others are inexistent. Both kinds of abstracts mostly use extending conjunctions, more especially positive additives. It can be concluded that the use of conjunctions varies in terms of their appropriateness. Inappropriate uses of conjunctions evince that EFL (English as a foreign language) learners had difficulty in using conjunctions in their writing. The students whose abstracts do not apply conjunctions connected the ideas in their abstracts using words and/or phrases which are excluded in the theoretical framework of this study. More similarities than differences in the ways conjunctions being used in the two kinds of abstracts prove that students from the same department of study had the same discourses.